2018
DOI: 10.1007/s42452-018-0068-x
|View full text |Cite
|
Sign up to set email alerts
|

In-situ synthesis and characterization of silver nanoparticle decorated cotton knitted fabric for antibacterial activity and improved dyeing performance

Abstract: This study reports the antimicrobial activity and improved dyeing performance of cotton knitted fabric by depositing silver nanoparticles on the surface. The cotton fabric is first treated with caustic soda (NaOH) of three different concentrations to activate the hydroxyl groups on the cellulose surface and then the nanoparticles are introduced on fabric surface by direct reduction of silver nitrate salt using ascorbic acid. The presence of silver nanoparticles on the fabric surface is clearly observed by scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
(31 reference statements)
2
18
0
Order By: Relevance
“…EDX analysis was performed to observe the elemental distributions on the surface of cotton fabrics coated with chitosan and nano-Ag particles and to detect the presence of nano-Ag particles on the fabric surface. Previous studies reported that 3 keV peaks attributed to the Ag formation signal were observed in the EDX analysis graph of the nano-Ag deposited fabric (Gharibshahi et al 2017, Tania et al 2019. In this study, the presence of the peak of the Ag element in the EDX spectrum of cotton fabrics confirmed the deposition of silver nanoparticles on the fabric.…”
Section: Sem and Edx Analysis Resultssupporting
confidence: 77%
“…EDX analysis was performed to observe the elemental distributions on the surface of cotton fabrics coated with chitosan and nano-Ag particles and to detect the presence of nano-Ag particles on the fabric surface. Previous studies reported that 3 keV peaks attributed to the Ag formation signal were observed in the EDX analysis graph of the nano-Ag deposited fabric (Gharibshahi et al 2017, Tania et al 2019. In this study, the presence of the peak of the Ag element in the EDX spectrum of cotton fabrics confirmed the deposition of silver nanoparticles on the fabric.…”
Section: Sem and Edx Analysis Resultssupporting
confidence: 77%
“…In many studied approaches to green in-situ AgNP phytosynthesis, the aggressive chemicals were used to prepare plant extracts, e.g. in methanol, ethanol and hexane as solvents, or in the presence of sodium hydroxide or acetic acid, and therefore cannot be considered as fully green synthesis processes (Rehan et al 2020;Yu et al 2020;Logeswari et al 2015;Velmurugan et al 2017;Tania et al 2018). However, there are some studies in which only silver precursors and plant water extracts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 (a) shows the untreated fabric where no Ag nanoparticle exists. It can be noted that this method shows more deposition of Ag nanoparticles than that of other in-situ deposition methods of our previous work [12,22]. By initial observation, SEM image proves the successful immobilization of Ag nanoparticles into the cotton fabric surface.…”
Section: Characterization Of Fabricmentioning
confidence: 57%
“…Different ways are available to modify the textile surface for better performance of nanoparticle deposition. Fiber modi cation in the case of in-situ nano deposition also offers a greater opportunity for instant xation [12]. In this research, the fabric is modi ed chemically by using dopamine hydrochloride.…”
Section: Introductionmentioning
confidence: 99%